1999
DOI: 10.1159/000006977
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Endogenous Sex Hormone Levels, Lipoproteins and Coronary Atherosclerosis in Men Undergoing Coronary Angiography

Abstract: This study was carried out in order to investigate the relationship between endogenous sex steroid hormones and coronary artery disease (CAD). Three hundred and thirty-seven men undergoing coronary angiography were enrolled in the study. Total testosterone, estradiol, free testosterone levels in men with CAD (n = 213) were compared to those of men without CAD (n = 124). No significant differences were found in the serum concentrations of estradiol, total and free testosterone and serum lipid profile between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
1
25
3
1
Order By: Relevance
“…Helaly et al found that patients with ACS had lower values of fT in comparison to control group [8]. In contradiction with these studies, as evidenced in our study, there are many studies showing no correlation between CAD and testosterone level [9][10][11][12][13][14]. These different results may be due to differences of assay methods and testosterone types.…”
Section: Discussioncontrasting
confidence: 99%
“…Helaly et al found that patients with ACS had lower values of fT in comparison to control group [8]. In contradiction with these studies, as evidenced in our study, there are many studies showing no correlation between CAD and testosterone level [9][10][11][12][13][14]. These different results may be due to differences of assay methods and testosterone types.…”
Section: Discussioncontrasting
confidence: 99%
“…There is an inverse relationship between endogenous serum testosterone levels and coronary heart disease in males (8,11,12) although all studies cannot confirm this finding (6,13,14,15,16), and the direction of causality of the phenomenon remains unclear. Moreover, a decreased serum testosterone concentration has been shown to be associated with acute ischemic strokes, infarct size and mortality (17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…253 No consistent relationship between the levels of free or total testosterone and coronary atherosclerosis in men undergoing coronary angiography has been observed. 151,254 Testosterone-replacement therapy does not increase the incidence of cardiovascular disease or events such as myocardial infarction, stroke, or angina. 88 A meta-analysis 255 in 2007 concluded that the current available evidence shows no association between testosterone replacement therapy and cardiac events.…”
Section: Dovepressmentioning
confidence: 99%